Data Analytics and Management in Data Intensive Domains 23rd International Conference, DAMDID/RCDL 2021, Moscow, Russia, October 26-29, 2021, Revised Selected Papers - Pozanenko, Alexei; Stupnikov, Sergey; Thalheim, Bernhard; Mendez, Eva.; Kiselyova, Nadezhda (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the post-conference proceedings of the 23rd International Conference on Data Analytics and Management in Data Intensive Domains, DAMDID/RCDL 2021, held in Moscow, Russia, in October 2021*. The 16 revised full papers were carefully reviewed and selected from 61 submissions. The papers are organized in the following topical sections: problem solving infrastructures, experiment organization, and machine learning applications; data analysis in astronomy; data analysis in material and earth sciences; information extraction from text * The conference was held virtually due to the COVID-19 pandemic.
Problem Solving Infrastructures, Experiment Organization, and Machine Learning Applications -- MLDev: Data Science Experiment Automation and Reproducibility Software -- Response to Cybersecurity Threats of Informational Infrastructure Based on Conceptual Models -- Social Network Analysis of the Professional Community Interaction - Movie Industry Case -- Data Analysis in Astronomy -- Cross-Matching of Large Sky Surveys and Study of Astronomical Objects Apparent in Ultraviolet Band Only -- The Diversity of Light Curves of Supernovae Associated with Gamma-Ray Bursts -- Application of Machine Learning Methods for Cross-Matching Astronomical Catalogs -- Pipeline for Detection of Transient Objects in Optical Surveys -- VALD in Astrophysics -- Data Analysis in Material and Earth Sciences -- Machine Learning Application to Predict New Inorganic Compounds - Results and Perspectives -- Interoperability and Architecture Requirements Analysis and Metadata Standardization for a Research Data Infrastructure in Catalysis -- Fast Predictions of Lattice Energies by Continuous Isometry Invariants of Crystal Structures -- Image Recognition for Large Soil Maps Archive Overview: Metadata Extraction and Georeferencing Tool Development -- Information Extraction from Text -- Cross-lingual Plagiarism Detection Method -- Methods for Automatic Argumentation Structure Prediction -- A System for Information Extraction from Scientific Texts in Russian -- Improving Neural Abstractive Summarization with Reliable Sentence Sampling.
Keywords: Data mining; Artificial intelligence; Application software; Social sciences-Data processing; Image processing-Digital techniques; Computer vision; Software engineering; Data Mining and Knowledge Discovery; Artificial Intelligence; Computer and Information Systems Applications; Computer Application in Social and Behavioral Sciences; Computer Imaging, Vision, Pattern Recognition and Graphics; Software Engineering